Trenitone Asitrogen Peritoneal Carcinomatosis Treated with Trenimon - Pollak Götzl, Erich W (Cirugía del Uruguay, 2020)
A case of ascitogenous peritoneal carcinomatosis in which Trenimon's procedure was perfomed by the intraperitoneal intravenous and oral routes is reported upon